Effects of Trans-Cinnamaldehyde on Campylobacter and Sperm Viability in Chicken Semen after In vitro Storage - Liu, G.Q.; Donoghue , A.M.; Moyle, J.R.; Reyes-Herrera, I.; Blore, P.J.; Bramwell, R.K.; Yoho, D.E.; Venkitanarayanan, K.; Donoghue, D.J. (International Journal of Poultry Science, 2012)
Campylobacter is one of the leading causes of bacterial human acute gastroenteritis. These microorganisms are highly prevalent in poultry semen and may contribute to vertical transmission of the pathogen between the breeder hen and offspring. Unfortunately, strategies to reduce or eliminate these pathogens in poultry semen negatively impact sperm viability. Many plant essential oils have been reported to exhibit antimicrobial activity against bacteria, fungi and viruses. The objective of our study was to examine the efficacy of trans-cinnamaldehyde, the main component in cinnamon oil, to reduce Campylobacter concentrations in chicken semen. Semen was collected from roosters, pooled and diluted with semen extender, then divided into treatments: negative control (no Campylobacter, no trans-cinnamaldehyde), positive control (inoculated with Campylobacter, no trans-cinnamaldehyde) or treatments containing concentrations of 0.24, 0.12, 0.06, 0.03 or 0.015% trans-cinnamaldehyde. Treatment groups receiving Campylobacter were then immediately inoculated with ~105 cfu/mL of a wild-type Campylobacter jejuni and held at 4°C or 23°C for 2 h. Semen was stored at 4°C for an additional 24 h and assessed for Campylobacter concentrations and sperm viability at 2, 6 and 24 h utilizing SYBR 14/Propidium iodide live/dead stain and fluorescent microscopy. The study was replicated eight times. After 2h at 23°C a 2 log reduction in Campylobacter counts were observed in the 0.12 and 0.24% trans-cinnamaldehyde treatment groups compared to positive controls. In the 4°C treatments, no differences were observed between treatments and controls after 2 h. Samples evaluated after 24 h incubation in vitro at 4°C, showed significant reductions of Campylobacter counts in the 0.06, 0.03 or 0.015% trans-cinnamaldehyde treatments groups, while the 0.12 and 0.24% groups eliminated detectable Campylobacter counts. Sperm viability remained at 80% or above for all treatment groups. Trans-cinnamaldehyde reduced Campylobacter in semen, without detrimentally affecting sperm viability and might provide a practical solution to eliminate Campylobacter in poultry semen after in vitro storage.